The Iron-Responsive Fur Regulon in Yersinia pestis - Gao, He (American Society for Microbiology (ASM), 2008)
The ferric uptake regulator (Fur) is a predominant bacterial regulator controlling the iron assimilation functions in response to iron availability. Our previous microarray analysis on Yersinia pestis defined the iron-Fur modulon. In the present work, we reannotated the iron assimilation genes in Y. pestis, and the resulting genes in complementation with those disclosed by microarray constituted a total of 34 genome loci (putative operons) that represent the potential iron-responsive targets of Fur. The subsequent real-time reverse transcription-PCR (RT-PCR) in conjunction with the primer extension analysis showed that 32 of them were regulated by Fur in response to iron starvation. A previously predicted Fur box sequence was then used to search against the promoter regions of the 34 operons; the homologue of the above box could be predicted in each promoter tested. The subsequent electrophoretic mobility shift assay (EMSA) demonstrated that a purified His(6) tag-fused Fur protein was able to bind in vitro to each of these promoter regions. Therefore, Fur is a global regulator, both an activator and a repressor, and directly controls not only almost all of the iron assimilation functions but also a variety of genes involved in various non-iron functions for governing a complex regulatory cascade in Y. pestis. In addition, real-time RT-PCR, primer extension, EMSA, and DNase I footprinting assay were used to elucidate the Fur regulation of the ybt locus encoding a virulence-required iron uptake system. By combining the published data on the YbtA regulation of ybt, we constructed a concise Fur/YbtA regulatory network with a map of the Fur-promoter DNA interactions within the ybt locus. The data presented here give us an overview of the iron-responsive Fur regulon in Y. pestis.